Long-lived charge carrier dynamics in polymer/quantum dot blends and organometal halide perovskites - Nagaoka, Hirokazu (My University, 2015)
Solution-processable semiconductors offer a potential route to deploy solar panels on a wide scale, based on the possibility of reduced manufacturing costs by using earth-abundant materials and inexpensive production technologies, such as inkjet or roll-to-roll printing. Understanding the fundamental physics underlying device operation is important to realize this goal. This dissertation describes studies of two kinds of solar cells: hybrid polymer/PbS quantum dot solar cells and organometal halide perovskite solar cells. Chapter two discusses details of the experimental techniques. Chapter three and four explore the mechanisms of charge transfer and energy transfer spectroscopically, and find that both processes contribute to the device photocurrent. Chapter four investigates the important question of how the energy level alignment of quantum dot acceptors affects the operation of hybrid polymer/quantum dot solar cells, by making use of the size-tunable energy levels of PbS quantum dots. We observe that long-lived charge transfer yield is diminished at larger dot sizes as the energy level offset at the polymer/quantum dot interface is changed through decreasing quantum confinement using a combination of spectroscopy and device studies. Chapter five discusses the effects of TiO2 surface chemistry on the performance of organometal halide perovskite solar cells. Specifically, chapter five studies the effect of replacing the conventional TiO2 electrode with Zr-doped TiO2 (Zr-TiO2). We aim to explore the correlation between charge carrier dynamics and device studies by incorporating zirconium into TiO2. We find that, compared to Zr-free controls, solar cells employing Zr-TiO2 give rise to an increase in overall power conversion efficiency, and a decrease in hysteresis. We also observe longer carrier lifetimes and higher charge carrier densities in devices on Zr-TiO2 electrodes at microsecond times in transient photovoltage experiments, as well as at longer persistent photovoltages extending from ~millisecond to tens of sec. Finally, we characterize the combined effects of pyridine treatment and Zr-TiO2 on device performance and carrier lifetimes.
Thesis (Ph.D.)--University of Washington, 2014
Keywords: lead sulfide; photoinduced absorption; photovoltage; photovoltaics; Physical chemistry; Chemistry; chemistry